How human activity impacted manufacturing non-compliances: A multivariate analysis in a centralized cytotoxic preparation unit. (December 2021) - Cornet, Lucie; Gervaise, Caroline; Hugues, Marion; Menguy, Sandrine; Macé, Agnès; Tinquaut, Fabien; Forges, Fabien; Simoens, Xavier
Introduction: The aim of the study was to identify risk factors related to human errors in the preparation of anticancer drugs in order to improve the pharmaceutical process by setting corrective actions. Method: Risk factors which could increase the probability of error were identified: daily workload, workload on the previous day and subcontractors' workload, time slot of the preparation, understaffing, incidents which could affect workflow, individual experience of technicians and cleanrooms layout. Drug reconstitution or complex fabrications were also considered as risk factors. We used univariate and multivariate logistic regression analyses to screen for correlation between risks and errors. Result: Among 11 278 preparations analyzed, 115 were non-compliant. Univariate analysis shows significant variables: individual experience of technicians, technicians working in the same cleanrooms and technicians' rotations. 2 technicians are significantly associated with a higher risk of error and 5 with a lower risk. The multivariate analysis confirmed the conclusions of the univariate. Discussion: As expected, time slot of the manufacture, cleanrooms layout and some technicians increase the risk of error. Surprisingly, technicians' experience led to increase the risk. This study is a first approach to evaluate the human error aspect in non-compliant preparations, in order to optimize security of antineoplastic drugs preparations.